2019
DOI: 10.1037/pspi0000153
|View full text |Cite|
|
Sign up to set email alerts
|

The face of STEM: Racial phenotypic stereotypicality predicts STEM persistence by—and ability attributions about—students of color.

Abstract: Despite strong initial interest, college students—especially those from underrepresented minority (URM) backgrounds—leave STEM majors at high rates. Here, we explore the role of racial phenotypic stereotypicality, or how typical one’s physical appearance is of one’s racial group, in STEM persistence. In a longitudinal study, URM students were especially likely to leave STEM to the extent that they looked more stereotypical of their group; Asian American students were especially likely to leave STEM to the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 153 publications
1
50
0
1
Order By: Relevance
“…Traditionally marketed as a competitive and meritocratic field, research has shown that there is more bias in STEM professions than their non-STEM counterparts (Leath & Chavous, 2018; National Academies of Science, Engineering, and Medicine, 2016). STEM is also known to have a survival of the fittest culture that deemphasizes both structural racism and students’ raced and gendered identities, thus implying that students’ success is due solely to individual “intelligence” (M. J. Williams et al, 2019).…”
Section: Stem Higher Education: Founded On Eurocentric Ideologies Andmentioning
confidence: 99%
“…Traditionally marketed as a competitive and meritocratic field, research has shown that there is more bias in STEM professions than their non-STEM counterparts (Leath & Chavous, 2018; National Academies of Science, Engineering, and Medicine, 2016). STEM is also known to have a survival of the fittest culture that deemphasizes both structural racism and students’ raced and gendered identities, thus implying that students’ success is due solely to individual “intelligence” (M. J. Williams et al, 2019).…”
Section: Stem Higher Education: Founded On Eurocentric Ideologies Andmentioning
confidence: 99%
“…Specifically, Todorov and colleagues' seminal work on impression formation concluded that perceivers extract facial information on two fundamental dimensions of dominance and trustworthiness Todorov et al, 2008). Yet these dimensions received inconsistent support in a global investigation conducted by Jones et al (2019), who replicated the previous findings when using the original statistical approach but documented a novel third dimension when using a different statistical approach. Furthermore, Xie et al (2019) showed that the structure of face-based impressions differs by targets' race and gender.…”
Section: Broadening the Stimulus Set: Introducing The American Multiracial Faces Databasementioning
confidence: 99%
“…Although face-based perceptions range quite a bit in their actual accuracy, these perceptions form the basis for how people behave towards each other (Jaeger et al, 2019;Gunaydin et al, 2017). In addition, the traits conveyed by a person's face can predict their outcomes in important domains such as education (Williams et al, 2019), the criminal justice system (Chen et al, 2020;Eberhardt et al, 2006;Wilson & Rule, 2015, and healthcare (Mattarozzi et al, 2017). Therefore, face-based impression formation processes are of fundamental importance to understanding human interaction.…”
Section: Broadening the Stimulus Set: Introducing The American Multiracial Faces Databasementioning
confidence: 99%
“…Yet, these stakeholders often rely on shallow, racial perceptions to make judgments of Black students’ ability to succeed in academic majors, such as STEM. Williams and colleagues (2019) demonstrated that Black students who were more stereotypically phenotypical of their racial group were rated as having lesser STEM ability, especially when raters were not concerned about appearing prejudiced. Once again, these perceptions matter.…”
Section: Discussionmentioning
confidence: 99%